The Influence of Reading Interest on The Learning Achievement of Fifth Grade Students at Teratak Elementary School - Oktorina, Ririn; Habibi, Mhmd.; Risnawati, Risnawati (FKIP-Universitas Riau, 2023)
The purpose of this research is to find out whether there is a relationship between the level of students' interest in reading and their academic achievement. Interest in reading is treated as an independent variable in this study, while learning achievement is treated as the dependent variable. This study uses an ex-post facto design and a quantitative approach to analyze the data. The participants in this study were all fifth grade students at public elementary school 009 Teratak, Rumbio Jaya District, Kampar Regency. The number of students is 33. Various methods, including questionnaires and careful documentation, were used to collect the data used in this study. A direct application of linear regression analysis was chosen as the method for processing the data. According to the findings of this study, interest in reading turned out to have a positive effect on the learning achievement of fifth grade students at public elementary school 009 Teratak. The contribution value that can be obtained through reading interest is 21,2 percent. The influence of reading interest on the level of student achievement is calculated into high scores based on research findings, especially by observing the pattern that emerges from the distribution of their test scores. Based on the findings of this study, one can draw the conclusion that students' level of interest in reading has an impact on their academic performance. Increasing students' interest in reading is a form of long-term investment that can help students in the learning process and can also support students in achieving a higher level of learning achievement than before.